2013
DOI: 10.1371/journal.pone.0056365
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Association between KCNB1 rs1051295 and Type 2 Diabetes and Its Related Traits in Chinese Han Population

Abstract: Since the KCNB1 encoding Kv2.1 channel accounts for the majority of Kv currents modulating insulin secretion by pancreatic islet beta-cells, we postulated that KCNB1 is a plausible candidate gene for genetic variation contributing to the variable compensatory secretory function of beta-cells in type-2 diabetes (T2D). We conducted two studies, a case-control study and a cross-section study, to investigate the association of common single-nucleotide polymorphisms (SNPs) in KCNB1 with T2D and its linking traits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
2
7
1
Order By: Relevance
“…rs1051295: Compared with genotype CC, both of genotype TT ( P = 0.03, b = 0.06 (0.01, 0.12)) and TC ( P = 0.10, b = 0.10(-002, 0.22)) was associated or inclined to be associated with increased serum TG levels, in line with our previous report [ 2 ]. We also found that genotype TT tended to be associated with increased BMI ( P = 0.09, b = -0.22 (-0.48, 0.04)), HOMA-IR ( P = 0.09, b = 0.04(-0.01, 0.09)), FINS ( P = 0.11, b = 2.92(-0.06, 0.65)) and HOMA-B ( P = 0.09, b = 5.66(-0.86, 12.18)) compared with genotype CC (Table 1 ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…rs1051295: Compared with genotype CC, both of genotype TT ( P = 0.03, b = 0.06 (0.01, 0.12)) and TC ( P = 0.10, b = 0.10(-002, 0.22)) was associated or inclined to be associated with increased serum TG levels, in line with our previous report [ 2 ]. We also found that genotype TT tended to be associated with increased BMI ( P = 0.09, b = -0.22 (-0.48, 0.04)), HOMA-IR ( P = 0.09, b = 0.04(-0.01, 0.09)), FINS ( P = 0.11, b = 2.92(-0.06, 0.65)) and HOMA-B ( P = 0.09, b = 5.66(-0.86, 12.18)) compared with genotype CC (Table 1 ).…”
Section: Resultssupporting
confidence: 88%
“…Our recently reported case–control study in Chinese Han population showed a strong association of KCNB1 rs1051295 genotype TT with an increased risk of becoming afflicted with metabolic syndrome leading to T2D. Specifically, we showed the genotype TT of this SNP was associated with several metabolic traits of metabolic syndrome, including increased waist to hip ratio (WHR), fasting insulin (FINS) levels, increased serum triglyceride (TG) levels, and decreased insulin sensitivity at basal condition [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used genotype data from the CHB panel (Han Chinese in Beijing) of the phase ⅡHapMap Project to select tag SNPs within the range of 5000bp upstream of the initiation codon and 5000bp downstream of the termination codon of the PLA2G2A gene on the basis of the following criteria: (1) r 2 linkage disequilibrium (LD) statistic >0.8 (Huang et al, 2009;Zhang et al, 2013); (2) minor allele frequency (MAF) >0.1; In addition to 13 tag SNPs in the PLA2G2A gene, 4 other tag SNPs (rs20417, rs689466, rs5275and rs12042763) in the PTGS2 gene were added to the set of markers, based on their functional relevance and significant association with cancer in previous studies (Zhang et al, 2005;Liu et al, 2006;Salinas et al, 2010;Liang et al, 2011;. Detailed information for all the tag SNPs including genomic position, genic position, minor allele frequency, and Hardy-Weinberg equilibrium are shown in Table 1.…”
Section: Tag Snps Selection and Genotypingmentioning
confidence: 99%
“…Variants of the PREX1 gene on chromosome 20q12-13.1were associated with increased risk of diabetes mellitus type 2 and increased BMI in a cohort of European Americans 65 , through mechanisms are yet insufficiently understood 66 . Variants of the KCNB1 gene in humans are associated with increases of waist to hip ratio, fasting insulin, and triglycerides, as well as decreased insulin sensitivity 67,68 . Mechanistically, the KCNB1-encoded Kv2.1 and other K + v are important for the fine-tuning of the release of cellular insulin and other hormones or neurotransmitters, and have both inhibitory (through re-polarization of the membrane potential 69 ) and stimulating (through interaction with the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex) 70-73 effects on exocytotic mechanisms.…”
Section: Discussionmentioning
confidence: 99%